Hepatitis B and C Infections in Pregnant Women Undergoing Chorionic Villus Sampling in Pakistan (2023–2024): Hepatitis B and C Infections in Pregnant Women Undergoing Chorionic Villus - Parveen, Shahida; Khan, Bushra; Aziz, Amna; Razia, Tehreem; Sana, Rida; Mehmood, Rubaida (Pakistan Journal of Health Sciences, 2025)
Pregnant women with high viral loads of HBV and HCV are at increased risk of vertical transmission and long-term complications. Objectives: To determine the disease burden of hepatitis B and C infections in pregnant women who underwent chorionic villus sampling (CVS). Methods: A comparative cross-sectional study was done in MINAR Cancer Hospital, Multan, from January 2023 to June 2024 for eighteen months using a non-probability purposive sampling technique. 1000 pregnant ladies who were scheduled for CVS were included after fulfilling the exclusion and inclusion criteria. Participants were divided into two age groups: 16–25 years and 26–50 years. Blood samples were taken and tested for HBV and HCV infections using commercial kits. The data were recorded and explored using SPSS version 24. Results: The participants had an average age of 27.78 ± 4.93 years (range: 16–46 years). HBV DNA was detected in 21 women (2.1%), while 66 (6.6%) tested positive for HCV RNA, leading to a total infection rate of 8.7%. Participants were divided into two age groups: 16–25 years (n=370) and 26–50 years (n=630). HBV infection rates were 1.6% and 2.38% in younger and older groups, respectively (P=0.418), while HCV infection rates were significantly higher in the older group (7.77% vs. 4.59%, p=0.04). Conclusion: It was concluded that the study highlights a significant prevalence of HBV and HCV infections in pregnant women undergoing CVS, emphasizing the need for routine screening and preventive strategies to reduce vertical transmission.